THE DEVELOPMENT OF ADOBE FLASH MEDIA ASSISTED LEARNING INSTRUMENT TO TRAIN STUDENT’S PROCESS SCIENCE SKILL - Jane Koswojo; Sugimin Wahyu Winata; - Wasis (Widya Mandala Surabaya Catholic University, 2018)
This study aims to describe the development of feasible Adobe Flash-based learning media with optical instrument materials to train students' processing science skills. This is a developmental research with a 4D model and on the subjects of this research were Grade X students in Kartika Wijaya Surabaya Senior High School academic year 2016/2017 with a developmental testing using one group pretest-posttest design. The data obtained were quantitatively and qualitatively analyzed. The results of the analysis showed that learning media with supporting tools in the form of the syllabus, lesson plan, worksheet, and process science skills assessment were feasible to be used. Learning media along with supporting tools that have been developed for a jigsaw-type cooperative learning model can train the students’ process science skills. The students' process science skills were improved with the average N-gain score of 0.74 in the first replication and 0.88 in the second replication, they were categorized as a high category. The conclusion of this research was that Adobe Flash-based Physics learning media with materials of optical instrument could be used in the learning process and to train students’ process science skill.